DETERMINATION OF WORK MOTIVATION, LEADERSHIP, AND TRAINING WITH WORK CULTURE AS AN INTERVENING VARIABLE ON PERFORMANCE IN REGIONAL REVENUE AGENCY BATAM CITY - Reny Nozariyanti; Angelina Eleonora Rumengan; Indrayani; Muammar Khaddafi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the Determination of Work Motivation, Leadership, and Training with Work Culture as Intervening Variables on Performance at the Regional Revenue Agency of Batam City. The research method used is descriptive method with a quantitative approach. This descriptive method involves collecting data to test hypotheses or answer questions about people's opinions on an issue or topic. Data collection was carried out using a questionnaire instrument which was distributed to 102 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3 software. The results showed that the effect of work motivation on performance had a P-value of 0.026 <0.05, so it can be stated that the effect of work motivation on performance is significant. The influence of the leadership variable on performance has a P-value of 0.000 <0.05, so it can be stated that the influence of leadership on performance is significant. The effect of the training variable on performance has a P-Values ​​of 0.001 <0.05, so it can be stated that the effect of training on performance is significant. The influence of work culture variables on performance has a P-value of 0.025 <0.05, so it can be stated that the influence of work culture on performance is significant. The influence of work motivation variables on work culture has a P-Values ​​of 0.008 <0.05,